Limonene as a Multi-Target Antibiofilm and Quorum Sensing Inhibitor Against Pseudomonas aeruginosa (Journal of Basic and Applied Research in Biomedicine, 2024)
Pseudomonas aeruginosa, a common causative pathogen of nosocomial infections, has recently evolved multidrug resistance, creating an urgent demand to develop alternate antimicrobials targeting virulence systems. In this study, we elucidate the inhibitory effects of limonene, a monoterpene abundantly present in citrus essential oils, on biofilm formation and quorum sensing systems of P. aeruginosa. The determination of limonene antibacterial activity determined the MIC to be 0.63 mg/mL. Limonene showed strong antibiofilm activity, inhibiting by 97.18% at MIC, while at sub-MIC (0.078 and 0.039 mg/mL), it also demonstrated good efficacy. Mechanistic analyses revealed that limonene inhibits biofilm formation via the modulation of bacterial aggregation, surface hydrophobicity, swarming motility, and extracellular polymeric substance (EPS) release. Under sub-MIC levels, limonene also inhibited important virulence factors like pyocyanin, rhamnolipids, and LasA protease. Additionally, limonene played a role in interrupting quorum sensing communication, as it inhibited violacein biosynthesis by Chromobacterium violaceum and decreased acyl-homoserine lactone (AHL) synthesis in P. aeruginosa. High-throughput molecular analysis confirmed massive downregulation of pivotal quorum sensing genes (lasI/R and rhlI/R), ultimately pointing to limonene's remarkable property of interfering with bacterial signaling circuitry. These results highlight limonene as a multi-target pharmacological agent against P. aeruginosa, representing a promising alternative to classical antibiotics. More studies are required to determine its mechanisms of action, effects on other quorum sensing regulated genes, and responsiveness in clinical settings. These findings add to the mounting evidence supporting the use of natural compounds against antibiotic resistance and biofilm-associated infections.